Regionalism in Post-Suharto Indonesia - Maribeth Erb, , Priyambudi Sulistiyanto and Carole Faucher (RoutledgeCurzon, 2005)
The regional autonomy laws of 1999 (Undang-Undang Otonomi Daerah),1 that were implemented in January 2001, brought a great deal of hope to those people in Indonesia who had been crying out for reformation of the government and the laws of the land since well before the fall of the long-serving President Suharto in May 1998. The highly centralistic government of the New Order, which kept close control over the use of resources in the various regions in Indonesia, as well as political and economic developments of various kinds, was increasingly seen as exerting a stranglehold on the lives of the Indonesian people. Especially outside Java, there were many who felt that they had never really enjoyed the fruits of 30 years of New Order Development, but instead bore the brunt of corruption, collusion and nepotism from the centre. The New Order regime emerged out of the chaos and massacres of 1965, following, reputedly, an ‘attempted coup’ by the Communist Party. Several months of massacres followed the claim that the communists were trying to take over Indonesia, and out of this threat and the ensuing chaos, was born a regime based on fear, and the created need for order and stability. Subsequently, the New Order government ruled, in what van Klinken characterizes very aptly as a ‘state of emergency’ (1999:62), for 32 years, where danger was believed to be ever present and where it was suspected that the masses hid potential enemies. The populace was also presented as a source of latent chaos and anarchy. The only hope for security, order and stability was a firm state and a highly centralized regime.